Effect of volume of gold chloroauric acid on size, shape and stability of biosynthesized AuNPs using aqueous Elaeis guineensis (oil palm) leaves extract - Ahmad, T. (Universiti Malaysia Pahang, 2018)
Biosynthesis of gold nanoparticles (AuNPs) using plant extracts has been receiving considerable attention of researchers due to their environmental friendly, low cost and renewability features. AuNPs were successfully synthesized at ambient conditions using aqueous Elaeis guineensis (oil palm) leaves extract without addition of any chemical agent. UV-Vis spectrophotometer, DLS and TEM were used to characterize the phytosynthesized AuNPs. FTIR was carried out to identify the functional groups involved in reduction of gold ions and stabilization of AuNPs. Hydrodynamic diameter was found to be reduced from 69± 39.80 nm to 55.22 ± 42.86 nm with an increase in the volume of gold chloroauric acid (1.53 mM) from 1.0 mL to 2.0 mL with fixed volume of oil palm leaves extract respectively. Size enlargement was observed from 60 ±43.76 nm to 123.5 ±110 nm with further increase in the volume of gold chloroauric acid from 3.0 mL to 5.0 mL respectively. Zeta potential (surface charge) of AuNPs was found to be reduced from -20 ± 6.80 mV to -15 ± 6.15 mV with an increase in the volume of gold chloroauric acid from 1.0 mL to 5.0 mL respectively. TEM results showed the formation of well scattered spherical, triangular and nonspherical shaped AuNPs by using 3.0 mL of gold chloroauric acid with an average particle diameter of 36.84 ± 9.0 nm. FTIR results revealed the role of phenolic, carboxylic and amides functional groups in reduction of gold ions to form AuNPs and their stabilization. Hence, ploydisperse AuNPs synthesized using Elaeis guineensis (oil palm) leaves with alterable morphology and good stability can be efficiently employed in medical and industrial applications. © Universiti Malaysia Pahang, Malaysia.